Effects of Two-Tier Self-Explanation and Attention Cueing Strategy on the Learning Achievement in Distance Multimedia Learning - Kuo, Yu-Chen; Lin, Hao-Chiang Koong; Tsai, Wei-Wei; Lin, Yu-Hsuan; Li, Cheng-Tsung (Frontiers in Education, 2022)
Distance learning becomes the new trend of development. When learners conduct distance learning, the features and the free status of distance learning make it easy for students to become distracted or unfocused on their learning. Therefore, design a material with cues based on the “Central Cue” and “Peripheral Cue” from the “Attentional Cuing Paradigm” to explore two cues which representing “endogenous” and “exogenous” attentional cueing by using multimedia video learning, whether it can effectively enhance the focus on the target area of interest (AOI) and the impact of the learning achievements and varieties. Detect learners’ eye movements and patterns by an eye tracker to analyze the relationship between learners’ watching patterns and learning achievements. In addition, will use two-tier testing and combined with self-explanation prompts to design, including the menu-based self-explanation strategy on the first level and the open-ended self-explanation strategy on the second level. Explore whether the two-tier self-explanation strategy will have better self-explanation learning achievements than the single-tier self-explanation strategy or not. The results show that learners using the central cue representing endogenous attentional cueing can effectively focus on the target AOI. The two-tier self-explanation strategy can help learners improve their learning achievement, learning motivation, and reflection.